ROLE OF SOME AROMATIC ESSENTIAL OIL ON IMMUNE STATUS AGAINST INFECTIOUS BRONICHITIS VACCINE AND LIPID PROFILE OF BROILER CHICKEN - Ulaiwi, A. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study evaluates the role of some aromatic essential oil (AEOs) (Eucalyptus oil, Mint oil, L-Menthol, and Thyme oil) with different methods of administration,  antibody titer of  infectious bronchitis virus (IBv) vaccine with different routes of vaccination, and value of total lipid profile. The study is designed as follows { T1:Oral method for each them  (AEOs) (0.2 ml/L) daily + vaccination against IBv-H120.T2: Spray method for each them (AEOs) (2 ml/L) twice weekly + vaccination against IBv-H120.T3: Spray method (AEOs) (2 ml/L) twice weekly plus oral method (AEOs) (0.2 ml/L) daily with oral vaccination IBv-H120.T4: Spray method (AEOs) (2 ml/L) twice weekly plus oral  method (AEOs) (0.2 ml/L) daily with oral vaccination IBv-H120.with spray vaccination against IBv-H120.T5:Oral method (AEOs) (0.2 ml/L) daily without vaccination.T6:Spray method (AEOs) (2 ml/L) twice weekly without vaccination.T7:Control negative (not treated and not vaccinated)}. The result of IBv titer showed that T4 and T2 had a significant difference among groups and in different ages. Also the result of lipid profile showed T3 and T4 had significant difference among groups. In conclusion the spray method of vaccination with different route of administration of (AEOs) was given the best antibody titer against IBv., and the mixing rout of administration of (AEOs) on total lipid profile (Cholesterol, triglyceride, HDL, VLDL and LDL) was the best on the single rate of administration of (AEOs).